2012
DOI: 10.1002/bdrb.21005
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2‐Mediated Resistance to Oxidant‐Induced Redox Disruption in Embryos

Abstract: Events that control developmental changes occur during specific windows of gestation and if disrupted, can lead to dysmorphogenesis or embryolethality. One largely understudied aspect of developmental control is redox regulation, where the untimely disruption of intracellular redox potentials (E(h) ) may alter development, suggesting that tight control of developmental-stage-specific redox states is necessary to support normal development. In this study, mouse gestational day 8.5 embryos in whole embryo cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…As a member of transcription factor, Nrf-2 was shown to play a critical coordinator as regulating the redox balance and protecting cells against oxidative and inflammatory lesions32. Nrf-2 exerts its balancing effects through regulating the expression of detoxification enzymes and antioxidant proteins, such as HO-1 and Trx-1, in response to a wide range of oxidant/ antioxidant/ electrophilic stimuli to protect the body33, 34. Additionally, Nrf-2/Trx-1 axis was demonstrated to modulate apoptosis-related signaling pathway through binding with relevant factors35.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of transcription factor, Nrf-2 was shown to play a critical coordinator as regulating the redox balance and protecting cells against oxidative and inflammatory lesions32. Nrf-2 exerts its balancing effects through regulating the expression of detoxification enzymes and antioxidant proteins, such as HO-1 and Trx-1, in response to a wide range of oxidant/ antioxidant/ electrophilic stimuli to protect the body33, 34. Additionally, Nrf-2/Trx-1 axis was demonstrated to modulate apoptosis-related signaling pathway through binding with relevant factors35.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that activation of the cellular antioxidant system via the Keap1-Nrf2 pathway is associated with SFA-induced lipotoxicity. Recently, SFN was used as an antioxidant that activates phase II enzymes via the Keap1-Nrf2 pathway (Fu et al, 2013;Harris & Hansen, 2012;Thimmulappa et al, 2002). As expected, pretreatment with SFN significantly decreased palmitate-or stearic acid-induced EA.hy926 cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor (erythroidderived 2)-like 2 (Nrf2) is an essential regulator of cytoprotective responses to oxidative stress and upregulates many genes associated with the regulation of intracellular redox states and ROS detoxification. Nrf2 regulates many key redox enzyme genes, including nicotinamide adenine dinucleotide phosphate (NADPH), glutathione S-transferase (GST), γ-glutamylcysteine synthetase (GCS), uridine diphosphate-glucuronyl transferase (UGT), and epoxide hydrolase (Harris & Hansen, 2012;Kwak, Itoh, Yamamoto, & Kensler, 2002;Thimmulappa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that activation of NFE2L2 in ethanol-exposed mouse embryos is involved in increased detoxifying and antioxidant enzymes (Harris & Hansen, 2012). Recently Lin et al (2018) reported that inhibition of NFE2L2 by brusatol prevents early mouse embryo development by affecting cell cycle progression from G2 to M Phase.…”
Section: Introductionmentioning
confidence: 99%